Larger Volume and Higher Fat Content of the Pancreatic Head Are Predictive Factors for Postendoscopic Retrograde Cholangiopancreatography Pancreatitis. Issue 1 (January 2022) - Shintani, Shuhei; Inatomi, Osamu; Bamba, Shigeki; Takeda, Yoshiya; Fujimoto, Takehide; Ota, Shinichi; Tsuji, Yoshihisa; Kutsumi, Hiromu; Watanabe, Yoshiyuki; Andoh, Akira
Abstract : Objectives: Acute pancreatitis is the most critical complication of endoscopic retrograde cholangiopancreatography (ERCP). In this study, we investigated the association between the volume/fat content of the pancreatic head and the incidence of post-ERCP pancreatitis (PEP). Methods: We retrospectively enrolled 157 patients who underwent ERCP. The volume and fat content of the pancreas were calculated by multislice computed tomographic imaging by using a volume analyzer. Multivariate analysis was performed to identify risk factors for PEP. Results: The mean volumes of the whole pancreas and pancreatic head were significantly larger, and the fat content of the pancreatic head was significantly higher in the PEP group ( P < 0.01). There were no significant differences in the mean volume and fat content of the pancreatic body and tail in the PEP group. Multivariate analysis revealed that the pancreatic guidewire placement (odds ratio [OR], 12.4; P < 0.01), pancreatic head volume (OR, 5.3; P < 0.01), and the pancreatic head fat content (OR, 4.8; P < 0.01) were independent risk factors for PEP. Conclusions: The pancreatic head volume and fat content were independent predicting factors of PEP. Quantitative assessment of the pancreas may contribute to the prediction of PEP onset.